2020
DOI: 10.1186/s41256-020-00180-1
|View full text |Cite
|
Sign up to set email alerts
|

The association between area of residence and sufficient antenatal tetanus vaccination in women ages 15–49 in Afghanistan: an analysis of the 2015 DHS dataset

Abstract: Background Neonatal tetanus (NT) is a deadly nervous system disorder that is endemic to Afghanistan. Administering sufficient doses of tetanus toxoid containing vaccine (TTCV) during pregnancy can pass antibodies to the fetus and therefore prevent NT. Using survey data, we investigated the association between area of residence (urban or rural) and sufficient antenatal TTCV coverage among women aged 15–49 years in Afghanistan during their most recent pregnancy in the past 5 years that resulted in a live birth. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 17 publications
1
11
0
Order By: Relevance
“…Studies indicated the coverage of full vaccination was low among mothers and children in Afghanistan, especially in remote areas 27 , 28 . Prolong conflict, lack of health essential knowledge, illiteracy, misinformation, and parental refusal are the key barriers to get the vaccination 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Studies indicated the coverage of full vaccination was low among mothers and children in Afghanistan, especially in remote areas 27 , 28 . Prolong conflict, lack of health essential knowledge, illiteracy, misinformation, and parental refusal are the key barriers to get the vaccination 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Adequate tetanus vaccination among women of childbearing age was defined previously as either receiving two doses of tetanus toxoid vaccine in the last pregnancy, more than one dose within the latest 3 years of birth, more than two doses within the latest 5 years of birth, more than three doses within the latest within 10 years of birth, or more than four doses at any time [ 6 , 7 ]. Accordingly, the dependent variable (adequate tetanus vaccination) was coded as a binary (yes, no) for further analysis.…”
Section: Methodsmentioning
confidence: 99%
“…It has been estimated that antenatal tetanus vaccination can reduce neonatal mortality from tetanus by 94% [ 5 ]. For previously non-immunized adults or those with unknown immunization status, a total of five tetanus toxoid vaccine doses are recommended by the World Health Organization (WHO) to combat MNT [ 5 7 ]. Obtaining two doses of the tetanus toxoid vaccine is recommended during the first pregnancy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…19,36,37 In Afghanistan, a conflict-ridden country with difficult terrain and gender bias, TTCV coverage was found to be insufficient in 46% of women; 38.1% of women did not receive any ANC. 38 The percentage of home deliveries in rural and urban Afghan women was 75% and 35%, respectively. 39 An audit from Guinea and another from Pakistan pointed towards association of NT with low TTCV coverage, poor ANC, and unhygienic cord care practices.…”
Section: Barriers To Achieving Targets Of Mntementioning
confidence: 98%